Barriers to healthcare access and experiences of stigma: Findings from a coproduced Long Covid case‐finding study - Donna Clutterbuck; Mel Ramasawmy; Marija Pantelic; Jasmine Hayer; Fauzia Begum; Mark Faghy; Nayab Nasir; Barry Causer; Melissa Heightman; Gail Allsopp; Dan Wootton; M. Asad Khan; et al. (Wiley, 2024)
Abstract Background and Aim Long Covid is often stigmatised, particularly in people who are disadvantaged within society. This may prevent them from seeking help and could lead to widening health inequalities. This coproduced study with a Community Advisory Board (CAB) of people with Long Covid aimed to understand healthcare and wider barriers and stigma experienced by people with probable Long Covid. Methods An active case finding approach was employed to find adults with probable, but not yet clinically diagnosed, Long Covid in two localities in London (Camden and Merton) and Derbyshire, England. Interviews explored the barriers to care and the stigma faced by participants and were analysed thematically. This study forms part of the STIMULATE‐ICP Collaboration. Findings Twenty‐three interviews were completed. Participants reported limited awareness of what Long Covid is and the available pathways to management. There was considerable self‐doubt among participants, sometimes reinforced by interactions with healthcare professionals (HCPs). Participants questioned their deservedness in seeking healthcare support for their symptoms. Hesitancy to engage with healthcare services was motivated by fear of needing more investigation and concerns regarding judgement about the ability to carry out caregiving responsibilities. It was also motivated by the complexity of the clinical presentation and fear of all symptoms being attributed to poor mental health. Participants also reported trying to avoid overburdening the health system. These difficulties were compounded by experiences of stigma and discrimination. The emerging themes reaffirmed a framework of epistemic injustice in relation to Long Covid, where creating, interpreting and conveying knowledge has varied credibility based on the teller's identity characteristics and/or the level of their interpretive resources. Conclusion We have codeveloped recommendations based on the findings. These include early signposting to services, dedicating protected time to listening to people with Long Covid, providing a holistic approach in care pathways, and working to mitigate stigma. Regardless of the diagnosis, people experiencing new symptoms must be encouraged to seek timely medical help. Clear public health messaging is needed among communities already disadvantaged by epistemic injustice to raise awareness of Long Covid, and to share stories that encourage seeking care and to illustrate the adverse effects of stigma. Patient or Public Contribution This study was coproduced with a CAB made up of 23 members including HCPs, people with lived experience of Long Covid and other stakeholders.